Patterns of Care (Parenting) Children with Special Needs - Wira Bayu, Gede; Kusmariyatni, Nyoman (Journal of Education Reseach and Evaluation, 2019)
The purpose of this study was to investigate  the patterns of care of children with special needs in Sjakitarius Foundation Singaraja. The research employed a case study design, including 30 children with special needs, their parents, and teachers. The data were obtained through observation, interview, and document recording. Then the data were processed by using a snow ball technique. The study reveals three themes. Firstly, children with special needs had a tendency to have social interaction deficits (narrow, very limited) with a 74% presentation. They also experienced as many as 85% verbal and nonverbal communication disorders with repeat stereotype, and restricted (95%) stereotype or interest, as well as  behavior (100%), which occurs before the age of three. Secondly, the appropriate parenting pattern applied by parents to children with special needs is begun with (1) becoming a parent who deserves to imitate children, (2) not educating children at a cost that cannot be banned by their parents, (3) discipline still must be prioritized in guiding children, (4) putting forward and cultivating early on religion and good moral in children, (5) communication is done openly and fun with certain limitations, (6) avoiding negative actions toward children. Lastly, the appropriate parenting patterns applied by teachers to children with special needs are initiated by (1) becoming a creative and innovative teacher, (2) having unlimited patience, (3) being a positive model, (4)   communicating openly like a parent, (5) avoiding negative behaviours.